FP-AK-QIEA-R seed to help the convergence of PECO - Chire Saire J.E. (2018)
The author would like to thank Cesar M.V. Benítes of Bioinformatic Lab in UTFPR(Universidade Tecnologica Federal do Parana), Brasil.The author would like to thank CONCYTEC (Consejo Nacional de Ciencia, Tecnolog´ıa e Innovacion Tecnológica), by the financial supporting during Master Program.